Ara's amazing spinning wheel - Collins, David R. (Cleveland, Ohio : Modern Curriculum Press, 1987)
Ara, a male orb spider, hatches out his egg, grows maturity, spins his own web, finds a mate, and has the satisfaction of seeing his own baby spiders hatch.
Keywords: Spiders -- Juvenile Fiction; Spiders -- Fiction